2018
DOI: 10.1016/j.clon.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

A Dosimetric Comparison of Breast Radiotherapy Techniques to Treat Locoregional Lymph Nodes Including the Internal Mammary Chain

Abstract: Simple WT radiotherapy delivered in vDIBH achieves satisfactory coverage of the IMC while meeting heart and lung dose constraints. However, where higher isodose coverage is required, VMAT(vDIBH) is the optimal photon technique. The lowest OAR doses are achieved by PBT, in which the use of vDIBH does not improve dose statistics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 30 publications
10
72
0
Order By: Relevance
“…This reduces the dosimetric advantages offered by IMPT which nevertheless remains the technique that allows to minimize the dose to distal OARs for such patients. Interestingly, the advantages offered by IMPT seem not to be affected by the use of DIBH [6]. These results clearly indicate that the NTCP reduction expected with IMPT should also be reconsidered when comparing it to different IMXT techniques.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…This reduces the dosimetric advantages offered by IMPT which nevertheless remains the technique that allows to minimize the dose to distal OARs for such patients. Interestingly, the advantages offered by IMPT seem not to be affected by the use of DIBH [6]. These results clearly indicate that the NTCP reduction expected with IMPT should also be reconsidered when comparing it to different IMXT techniques.…”
Section: Discussionmentioning
confidence: 79%
“…The results obtained in our study hold when we compare IMPT with IMXT without the use of breath-control techniques. The recent in silico study on BC with nodal involvement by Rangers et al [6] confirmed that the mean dose to heart and lung in photon RT could be reduced by the use of DIBH, especially when combined with VMAT techniques. This reduces the dosimetric advantages offered by IMPT which nevertheless remains the technique that allows to minimize the dose to distal OARs for such patients.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…With the introduction of effective systemic therapy such as chemotherapy, anti-hormonal therapy, or targeted therapy, the oncologic outcomes have improved in patients with breast cancer [22,23]. In addition, advanced RT techniques enable precise targeting of the tumor, thereby allowing sufficient irradiation of the IMN region [24]. Such TNBC was defined as tumors that were negative for estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 on immunohistochemical staining of the breast tumor 2) Radiotherapy dose was calculated using the EQD2 assuming the α/β ratio of 3.5 Gy Abbreviations: IMN Internal mammary node, DFS Disease-free survival, TNBC Triple-negative breast cancer, FNABx Fine needle aspiration biopsy, ICS Intercostal space, EQD2 Biologically equivalent dose in 2 Gy fractions advances in the treatment of breast cancer have resulted in favorable tumor control in patients with cIMN+ breast cancer.…”
Section: Discussionmentioning
confidence: 99%